Peran Fasilitas Sekolah dalam Meningkatkan Kualitas Belajar Siswa di SMA Islam Galesong - Hestia Lestari; Arini Zainal; Muhammad Ikbal (Contemporary Education Review, 2026)
This research qualitatively analyzed the influence of school facilities on the learning quality of students at Galesong Islamic High School. School facilities, such as classrooms, libraries, and recreational areas, are considered to have an important role in creating a conducive learning environment. This study uses a qualitative approach with interviews as the main method to explore the perception of students, teachers, and school staff regarding the availability of facilities and their impact on students’ motivation and academic achievement. Reserch results show that adequate facilities, such as comfortable classrooms and complete libraries, increase students’ learning motivation. However, the limitattions of technological facilities and budgets are the main challenges in managing school facilities. This research recommends improving infrastructure and optimizing facility management to support technology based learning and improve the overall quality of education